Optimal design and enhancement of drive shaft mechanism in automobiles. (2020) - Kishore, R.; Gurusamy, P.; Nagendharan, S.; Subash, P.
Abstract: This paper reports on concentrating and creating an alternate mechanism for the existing differential mechanism in All Terrain Vehicles. The differential is a component in automobiles and other wheeled vehicles which allows the outer wheels to drive in a faster speed than the inner wheel drive during turns. This differential is a very essential part to turn the vehicle smoothly. An increase in one-wheel speed will be balanced by decreasing the speed of the other wheel. The vehicles with two drive wheels will face the problem when it comes to corners, here the drive wheel must be rotating in different speeds to achieve traction. Without Differential both driving wheels are forced to drive in same speed which results in very unpredictable and hectic handling issues and damages tires as well as roads also leads to possible failure of drive train. The existing differential have complicated mechanism and it takes huge space to occupy in the constrained cabin to overcome this design has been adapted by disengaging the drive shaft from the gearbox whenever the turns are taken. This drive shaft with engaging and disengaging mechanism has been adapted the disengaging driveshaft is a normal driveshaft or output shaft from gearbox with an additional mechanism attached to it. This mechanism is used to engage or disengage the wheels from the gearbox. This differential is light-weight, fast, less space-consuming and an economical solution for improving the turning radius as compared with existing differential gear system.